Ten years as boundary object: The search for identity and belonging as 'Hongkongers' - LOWE, John (Institutional Knowledge at Singapore Management University, 2023)
This article examines the complex process of symbolic boundary-making of ‘Hongkonger’ cultural identities through the lens of the controversial 2015 film Ten Years, which is a celebrated omnibus production comprised of five short segments that picture a dystopic end to Hong Kong’s cherished way of life in the year 2025. The article is premised on an interdisciplinary approach engaging with cultural studies and film studies. On one hand, it explores how Ten Years functioned as a boundary object, a vast terrain within which cultural identities of what it means to be a Hongkonger are constructed, banished, imagined, and performed under the rubric of bodily performatives. On the other hand, it offers blurring encounters into unfamiliar and precarious territories where the formation and formulation of Hongkonger identities and sense of belonging are negotiated, evacuated, and inhabited. In the end, the key tropes in Ten Years suggest that boundary work in post-Umbrella Hong Kong affectively negotiates with state-level nationalism advocated by the central government in Beijing through establishing and reformulating notions of ‘localism’ and Hongkonger identities.